The reverse modality effect: Examining student learning from interactive computer‐based instruction. (18th December 2013) - Inan, Fethi A.; Crooks, Steven M.; Cheon, Jongpil; Ari, Fatih; Flores, Raymond; Kurucay, Murat; Paniukov, Dmitrii
Abstract The purpose of this study was to explore the effects of modality on learning from multimedia instruction. This study utilized a factorial between‐subject design to examine the effects of modality on student learning outcomes, study patterns and mental effort. An interactive computer‐presented diagram was developed to teach the places of articulation in human speech. A total of 151 undergraduate students at a large southwestern university in USA participated in this study. Participants were randomly assigned to one of two modality conditions (ie, written text and spoken text). Data were obtained through surveys, student logs and knowledge tests. Findings revealed a reverse modality effect, wherein participants who studied with written text outperformed those who studied with spoken text.